Venoarterial extra corporeal membrane oxygenation experience in pediatric patients (Annals of Medical Research, 2022)
Aim: Extracorporeal membrane oxygenation (ECMO) is a life-saving strategy in pediatric patients when faced with cardiac or respiratory failure after cardiac surgery. In this article, we investigated the relationship between mortality and data, such as leukocyte, hematocrit (HCT), blood urea nitrogen (BUN), creatinine (CRE), albumin, lactate, c-reactive protein (CRP), systemic immune-inflammation index (SII), platelet-lymphocyte ratio (PLR), neutrophil-lymphocyte ratio (NLR), lactate- albumin ratio (LAR) which can be easily calculated from daily routine complete blood count and biochemistry tests of ECMO patients.Materials and Methods: We obtained hospital records of 12 pediatric and newborn patients who needed ECMO therapy. The patients were divided into two as non-survivors (Group NS) and survivors (Group S). Factors that may affect mortality were investigated.Results: Four patients (33%) were successfully weaned from ECMO and discharged. The remaining 8 patients died. 50% of the patients were male (n=6). While the median age was 28 (4-275) days in Group NS, the median age was 300 (300-960) days in Group S. Although not statistically significant (p=0.395), patients with younger age had a higher mortality rate. While the mean weight was 5.9±3.2 kg in Group NS, it was 6.9±3.2 kg in Group S. Postoperative PLR, SII in Group NS were higher compared to Group S. There was no statistically significant difference between the two groups. Bleeding rate was higher in Group NS than in Group S. There was an increase in postoperative NLR in Group NS compared to preoperative NLR.Conclusion: Although postoperative PLR and SII were found to be higher in Group NS, postoperative NLR was increased compared to preoperative NLR, and bleeding complications were more common in group NS, none of these parameters reached a statistically significant level.
Keywords: Extra corporeal membrane oxygenation; Mortality; Inflammatory markers